The Effect of Traditional Game-Based Play-Teach-Play Learning Method on Physical Fitness of Grade VI Elementary School Students - Diky Surya Irawan; Rahmat Permana; Budi Hendrawan (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effect and effectiveness of the traditional game-based play-teach-play learning method on the physical fitness of class VI students at SDN 2 Parumasan. This type of research uses quantitative with quasi-experimental methods. The design used in this study is the nonquivalent control group design. The population in this study were all students of class VI at SDN 2 Parumasan with a sample of 24 students. Data analysis techniques using observation, interviews, and tests. The assessment instrument used is the TKJI test instrument. Data analysis used paired sample t-test and independent t-test. Based on the results of the study, the results of this study obtained the calculation of the results in the paired sample t-test table at the pretest and posttest obtained sig (2-tailed) of 0.000. The decision making Ho is accepted if sig (2-tailed) 0.05. And for the independent sample t-test on the posttest of the experimental group and the posttest of the control group, a sig (2-tailed) of 0.000 is obtained. The decision made from these results is that Ho is accepted if sig (2-tailed) 0.05. Because the sig (2-tailed) value is 0.000, it means that 0.000 0.05 then Ho is rejected in other words Ha is accepted. Based on these data, it can be concluded that there is an influence of the traditional game-based play-teach-play learning method on physical fitness and is also effectively used for elementary school students in grade VI SDN 2 Parumasan.